Hydroxy-bridged resting states of a [NiFe]-hydrogenase unraveled by cryogenic vibrational spectroscopy and DFT computations - Caserta, Giorgio; Pelmenschikov, Vladimir; Lorent, Christian; Tadjoung Waffo, Armel F; Katz, Sagie; Lauterbach, Lars; Schoknecht, Janna; Wang, Hongxin; Yoda, Yoshitaka; Tamasaku, Kenji; Kaupp, Martin; Hildebrandt, Peter; et al. (Chemical science (Cambridge), 2021)
The catalytic mechanism of [NiFe]-hydrogenases is a subject of extensive research. Apart from at least four reaction intermediates of H 2 /H + cycling, there are also a number of resting states, which are formed under oxidizing conditions. Although not directly involved in the catalytic cycle, the knowledge of their molecular structures and reactivity is important, because these states usually accumulate in the course of hydrogenase purification and may also play a role in vivo during hydrogenase maturation. Here, we applied low-temperature infrared (cryo-IR) and nuclear resonance vibrational spectroscopy (NRVS) to the isolated catalytic subunit (HoxC) of the heterodimeric regulatory [NiFe]-hydrogenase (RH) from Ralstonia eutropha . Cryo-IR spectroscopy revealed that the HoxC protein can be enriched in almost pure resting redox states suitable for NRVS investigation. NRVS analysis of the hydrogenase catalytic center is usually hampered by strong spectral contributions of the FeS clusters of the small, electron-transferring subunit. Therefore, our approach to investigate the FeS cluster-free, 57 Fe-labeled HoxC provided an unprecedented insight into the [NiFe] site modes, revealing their contributions in a spectral range otherwise superimposed by FeS cluster-derived bands. Rationalized by density functional theory (DFT) calculations, our data provide structural descriptions of the previously uncharacterized hydroxy- and water-containing resting states. Our work highlights the relevance of cryogenic vibrational spectroscopy and DFT to elucidate the structure of barely defined redox states of the [NiFe]-hydrogenase active site. Active site vibrations of a [NiFe]-hydrogenase catalytic subunit are selectively probed by IR and NRV spectroscopy in two Ni II Fe II and Ni III Fe II resting states, contributing in combination with DFT modeling to rationalized structural candidates.